ANALISIS IMPLIKASI PERILAKU KOMUNIKASI DALAM HUBUNGAN IDOLA DAN PENGGEMAR MELALUI KOMUNITAS CHANNEL BTS DI WEVERSE - Agafanthy, Annysa Nur; Sonni, Alem Febri; Farid, Muhammad (Kinesik, 2024)
The massive use of mass media in the digital era makes us easily touched and influenced by the information held by mass media. Social media is one of the mass media that brings this influence to every user. Including the Weverse social media which is used by fans to interact with fellow communities and also their idols. So, to see the influence and implications of communication within the community, this research aims to analyze the influence of communication behavior between idols and fans in the BTS Channel community via Weverse social media. This research uses a descriptive-qualitative method using the basis of information processing theory where this research helps understand how humans process information and how this process influences human behavior. Data collection was carried out by observing and interviewing seven sources and their communication activities on Weverse social media. The results of this research reveal that the influence of communication between idols and fans can be seen through three aspects, namely cognitive, affective, and conative.